2020
DOI: 10.1186/s40359-020-00497-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported psychological distress during the COVID-19 outbreak in Nepal: findings from an online survey

Abstract: Background A lower respiratory tract infection caused by novel coronavirus termed as Corona Virus Disease (COVID-19) was first identified in China and subsequently took the form of pandemic. Studies on disease outbreak in the past and recent COVID-19 outbreak have demonstrated increased psychological distress and adverse impacts on mental health and psychological wellbeing of people. However, the impact of COVID-19 on psychological wellbeing of people in Nepal hasn't been studied adequately. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 36 publications
3
30
1
1
Order By: Relevance
“…As the results indicated, the current pandemic has imposed significant psychological effects on pregnant women and nearly two-thirds of participants reported severe psychological distress (IES-R score ≥37). This finding was higher compared with the results of previous studies conducted in Italy 37 and Nepal 38 and lower than the finding of a study done in Spain. 39 The discrepancy between these results might be accounted for by the difference in the used tools, study period and the standards of the health-care system among the countries in which the studies were conducted.…”
Section: Discussioncontrasting
confidence: 84%
“…As the results indicated, the current pandemic has imposed significant psychological effects on pregnant women and nearly two-thirds of participants reported severe psychological distress (IES-R score ≥37). This finding was higher compared with the results of previous studies conducted in Italy 37 and Nepal 38 and lower than the finding of a study done in Spain. 39 The discrepancy between these results might be accounted for by the difference in the used tools, study period and the standards of the health-care system among the countries in which the studies were conducted.…”
Section: Discussioncontrasting
confidence: 84%
“…Distress. The outbreak of COVID-19 was negatively associated with psychological distress responses of grief, hopelessness, posttraumatic symptoms, panic attacks, distress, anxiety, depression, loneliness, ambivalence, fear, stigma, and concern towards socioeconomic status [27,28]. A recent review of the research, which summarized 17 articles from different countries [29], further found a high prevalence of distress among the investigated general populations along with the COVID-19 pandemic.…”
Section: Psychological Coping Responsesmentioning
confidence: 99%
“…Another crucial scheme of this action plan is to develop and disseminate some materials to deal with mental wellbeing of teachers and learners, which is hardly taken into account in Nepal (Gnawali, 2020) although the study of Mahat and Khanal (2012) report that child mental health program implemented in schools have significant positive impact on students, school environment and teaching learning activities. The study of Gautam et al (2020) on the self-reported psychological distress during COVID-19 in Nepal equally emphasizes that there is a need of the formal body to address the appropriate mental health and psychological support response in Nepal.…”
Section: Emergency Action Plan For School Education 2020mentioning
confidence: 99%
“…For instance, it planned to collect data in relation to the access to resources by the first week of October; nonetheless, it has remained silent on how the data will be collected. The question emerges whether it was possible to collect the data in the given timeline given the situation that there was no usual practice of data collection, and there is high prevalence of psychological distress among the Nepalese during the pandemic (Gautam et al, 2020). Norris et al (2014) contend that the clarity on the issue is needed on any policy for the effective implementation.…”
Section: Emergency Action Plan For School Education 2020mentioning
confidence: 99%